Modeling and mitigation of long-range wakefields for advanced linear colliders. Issue 1 (1st January 2023) - Bosco, F; Camacho, O; Carillo, M; Chiadroni, E; Faillace, L; Fukasawa, A; Giribono, A; Giuliano, L; Majernik, N; Mostacci, A; Palumbo, L; Rosenzweig, J; et al.
Abstract: The luminosity requirements of TeV-class linear colliders demand use of intense charged beams at high repetition rates. Such features imply multi-bunch operation with long current trains accelerated over the km length scale. Consequently, particle beams are exposed to the mutual parasitic interaction due to the long-range wakefields excited by the leading bunches in the accelerating structures. Such perturbations to the motion induce transverse oscillations of the bunches, potentially leading to instabilities such as transverse beam break-up. Here we present a dedicated tracking code that studies the effects of long-range transverse wakefield interaction among different bunches in linear accelerators. Being described by means of an efficient matrix formalism, such effects can be included while preserving short computational times. As a reference case, we use our code to investigate the performance of a state-of-the-art linear collider currently under design and, in addition, we discuss possible mitigation techniques based on frequency detuning and damping.